2021
DOI: 10.1111/jhn.12907
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of three tools for malnutrition diagnosis in hospitalised patients: Comparison to subjective global assessment

Abstract: Background: Malnutrition is prevalent in hospital, and the Subjective Global Assessment (SGA) has been widely used for its identification. However, in the last decade, new tools were proposed by the Academy of Nutrition and Dietetics-American Society for Parenteral and Enteral Nutrition (AND-ASPEN), European Society for Clinical Nutrition and Metabolism (ESPEN) and Global Leadership Initiative on Malnutrition (GLIM). The diagnostic test accuracy of these tools has been scarcely investigated. Thus, we aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 55 publications
(147 reference statements)
3
14
1
4
Order By: Relevance
“…Therefore, timely nutritional assessment is needed for patients with diabetes and high-risk foot. Although Mini Nutritional Assessment (MNA) and subjective global assessment (SGA) are well-known nutritional assessment screening tools [ 20 , 21 ], they are not always easy to perform routinely in clinical practice. SGA is a well-established tool for nutritional assessment [ 20 ]; however, it is subjective and requires an evaluator with some training and specialized knowledge for accurate assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, timely nutritional assessment is needed for patients with diabetes and high-risk foot. Although Mini Nutritional Assessment (MNA) and subjective global assessment (SGA) are well-known nutritional assessment screening tools [ 20 , 21 ], they are not always easy to perform routinely in clinical practice. SGA is a well-established tool for nutritional assessment [ 20 ]; however, it is subjective and requires an evaluator with some training and specialized knowledge for accurate assessment.…”
Section: Discussionmentioning
confidence: 99%
“…La sensibilidad del GLIM en pacientes con riesgo nutricional (99,1 %) fue acorde a lo recomendado (≥ 80 %) y se especula que el GLIM detecta fácilmente al individuo desnutrido (34) . Lo mismo fue demostrado por Brito y colaboradores (86,6 %) y Burgel y colaboradores (86,8 %) (9,10) . En cambio, Allard y colaboradores encontraron una sensibilidad menor (61,30 %) (8) .…”
Section: Discussionunclassified
“…Las diferencias de sensibilidad y especificidad encontradas con otros estudios podrían deberse tanto a la disparidad en la metodología de los mismos como a la muestra de pacientes incluidos. A su vez, se debe considerar el desempeño de cada herramienta en las distintas poblaciones y las discrepancias en las técnicas de medición (8)(9)(10) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…17 Similarly, a comparison of ESPEN, the Global Leadership Initiative on Malnutrition (GLIM) and the American Society for Parenteral and Enteral Nutrition (ASPEN) tools with SGA found that ESPEN had low sensitivity, whereas ASPEN and GLIM had good agreement. 18 There are many other examples of tools being validated against each other in the literature 19 and, typically, these show only modest agreement and consistency and highlight the variation in sensitivity for predicting malnutrition risk. A systematic review of tools and their predictive validity in clinical practice found that MNA had good utility for assessing older adults but that no tool was able to both adequately screen nutritional status and predict poor nutritional outcomes.…”
Section: Future Prioritiesmentioning
confidence: 99%